Real-time Coupling Induced Linear and Nonlinear Light Dynamics in Coupled Microresonators - Pal, Arghadeep; Ghosh, Alekhya; Zhang, Shuangyou; Hill, Lewis; Yan, Haochen; Zhang, Hao; Bi, Toby; Alabbadi, Abdullah; Del’Haye, Pascal (Bragg Gratings, Photosensitivity, and Poling in Glass Waveguides, BGPP 2024 in Proceedings Advanced Photonics Congress 2024 - Part of Optica Advanced Photonics Congress, 2024)
We study the linear and nonlinear light interactions in coupled resonators. In our experiments, we can control the coupling gap between two resonators instantaneously to investigate symmetry breaking of hybridized counterpropagating modes.
CRIS-Team Scopus Importer:2025-02-04